Analisis Polisemi Adjektiva Warna dalam Bahasa Rusia - Yoga Adityo Nugroho; Ani Rachmat; Susi Machdalena (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This thesis is entitled “Analysis of Color Adjective Polysemy in Russian